The Perspectives of Diabetes Educators and Dietitians on Diet and Lifestyle Management for Gestational Diabetes Mellitus: A Qualitative Study - Amber J. Hanks; Clare Hume; Siew Lim; Jessica A. Grieger (Journal of Diabetes Research)
This study explores the knowledge and practice of diabetes educators and dietitians on diet and lifestyle management in women with gestational diabetes mellitus (GDM). Diabetes educators and dietitians were recruited from three maternity hospitals in Adelaide (Australia), through snowball and purposive sampling. Thirteen semistructured interviews were conducted, audio recorded, transcribed verbatim, and analysed for codes and themes. Four themes emerged: guidelines and resources, dietary intervention, management delivery, and communication. Diabetes educators and dietitians demonstrated consistent knowledge of nutritional management for GDM and uniform delivery methods. However, a lack of culturally diverse resources was highlighted, along with a lack of continuity of care across the multidisciplinary team. Barriers towards uptake of dietary intervention were reflected by diabetes educators and dietitians as women showing signs of guilt and stress and disengaging from the service. Further exploration on the knowledge and practice of diabetes educators and dietitians for GDM to best inform implementation strategies for knowledge translation of nutritional management is needed. The indication of language and cultural barriers and resources highlight an ongoing key priority area to support the care of women of ethnic minorities.